Effect of cycloplegia on the refractive status of children: the Shandong Children Eye Study - Hu, Yuan Yuan; Jonas, Jost B. (PLOS ONE, 2015)
Purpose: To determine the effect of 1% cyclopentolate on the refractive status of children aged 4 to 18 years. Methods: Using a random cluster sampling in a cross-sectional school-based study design, children with an age of 4-18 years were selected from kindergardens, primary schools, junior and senior high schools in a rural county and a city. Auto-refractometry was performed before and after inducing cycloplegia which was achieved by 1% cyclopentolate eye drops. Results: Out of 6364 eligible children, data of 5999 (94.3%) children were included in the statistical analysis. Mean age was 10.0±3.3 years (range: 4-18 years). Mean difference between cycloplegic and non-cycloplegic refractive error (DIFF) was 0.78±0.79D (median: 0.50D; range: -1.00D to +10.75D). In univariate analysis, DIFF decreased significantly with older age (P<0.001;correlation coefficient r:-0.24), more hyperopic non-cycloplegic refractive error (P<0.001;r = 0.13) and more hyperopic cycloplegic refractive error (P<0.001;r = 0.49). In multivariate analysis, higher DIFF was associated with higher cycloplegic refractive error (P<0.001; standardized regression coefficient beta:0.50; regression coefficient B: 0.19; 95% confidence interval (CI): 0.18, 0.20), followed by lower intraocular pressure (P<0.001; beta: -0.06; B: -0.02; 95%CI: -0.03, -0.01), rural region of habitation (P = 0.001; beta: -0.04; B: -0.07; 95%CI: -0.11, -0.03), and, to a minor degree, with age (P = 0.006; beta: 0.04; B: 0.009; 95%CI: 0.003, 0.016). 66.4% of all eyes with non-cycloplegic myopia (≤-0.50D) remained myopic after cycloplegia while the remaining 33.6% of eyes became emmetropic (18.0%) or hyperopic (15.7%) under cycloplegia. Prevalence of emmetropia decreased from 37.5% before cycloplegia to 19.8% after cycloplegia while the remaining eyes became hyperopic under cycloplegia. Conclusions: The error committed by using non-cycloplegic versus cycloplegic refractometry in children with mid to dark-brown iris color decreased with older age, and in parallel manner, with more myopic cycloplegic refractive error. Non-cycloplegic refractometric measures lead to a misclassification of refractive error in a significant proportion of children.